2010
DOI: 10.1021/ie101144h
|View full text |Cite
|
Sign up to set email alerts
|

Primarily Industrialized Trial of Novel Fibers Spun from Cellulose Dope in NaOH/Urea Aqueous Solution

Abstract: Faced with the serious pollution caused by the viscose method (use of CS 2 ), a primarily industrialized trial via a "green" wet-spinning process based on dissolution of cellulose in NaOH/urea aqueous solution precooled to -12.5 °C was performed. In a dissolution tank of 1000 L capacity, the cellulose could be dissolved completely in the NaOH/urea system within 5 min, and cellulose fibers were spun successfully from the transparent dope. A 15:10 H 2 SO 4 /Na 2 SO 4 aqueous solution was adopted as the first coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 19 publications
(36 reference statements)
0
28
0
1
Order By: Relevance
“…Therefore, highly disrupted crystalline structure in the case of 5% cellulose film may infer that cellulose has been dissolved to a large degree at 5% concentration as compared to 10 and 15%. The vibration at 1427 cm −1 is ascribed as a crystalline absorption band and the vibration at 897 cm −1 in cellulose is assigned to the β‐linkage . The ratio of integrated peak area at two vibrations (1427 cm −1 : 897 cm −1 ) has been used as an empirical crystallinity index of cellulose .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, highly disrupted crystalline structure in the case of 5% cellulose film may infer that cellulose has been dissolved to a large degree at 5% concentration as compared to 10 and 15%. The vibration at 1427 cm −1 is ascribed as a crystalline absorption band and the vibration at 897 cm −1 in cellulose is assigned to the β‐linkage . The ratio of integrated peak area at two vibrations (1427 cm −1 : 897 cm −1 ) has been used as an empirical crystallinity index of cellulose .…”
Section: Resultsmentioning
confidence: 99%
“…XRD analysis was performed to characterize the crystalline structure of regenerated films. The XRD pattern of MCC shows characteristic peaks of native cellulose (cellulose I) at 14.7, 16.4, 22.7, and 34.5° corresponding to the crystal lattice of 1–10, 110, 200, and 400, respectively (Figure ). All XRD patterns of HD [Figure (a)] and FD [Figure (b)] regenerated films show a decrease in crystallinity as compared to MCC.…”
Section: Resultsmentioning
confidence: 99%
“…Solution state can be maintained for quite a long time . Novel cellulose silk, membrane, chromatographic column fillers, composite materials, and cellulose derivative were successfully prepared with this solution. However, there is still lack of systematic study about heat insulation performance of cellulose aerogel.…”
Section: Introductionmentioning
confidence: 99%
“…10 Various studies have shown that graphene/graphene oxide is a perfect material for the removal of dyes due to its good mechanical strength, large surface area, 2D structure, abundant surface functional groups, and its electrostatic interaction with cationic dyes. [11][12][13] However, the preparation of graphene from graphite is expensive and using toxic chemicals. A biologically derived graphene is possibly the most reasonable and chemically most adaptable graphene.…”
Section: Introductionmentioning
confidence: 99%